Comparative And Analytical Study of Al-sair-ul-Kabir and Geneva Convention about Civilian Rights in War - Qaisar Iqbal (`, 2025)
War is a painful reality that every wise individuals wishes to avoid, yet in practice, it remains unavoidable. In Islam, life is viewed as a test, and Muslim strive to become exemplary figures for those seeking to live peacefully, away from conflict. The ongoing battle between good and evil will persist, yet efforts can be made to minimize war’s impact, even though its existence cannot be denied. When conflicts arise and fighters are wounded or civilians are effected and no longer participating in the conflict, it is a moral responsibility to move them to safety and to offer humanitarian aid to those harmed. The International Committee of the Red Cross (ICRC), a neutral humanitarian organization, was founded in 1860 with this vision of protecting human dignity during conflict. After extensive discussions and efforts, the ICRC established four key humanitarian principles to maintain neutrality during war and violence. Remarkably, nearly eight centuries earlier Imam Hasan Al-Shaibani authored “Al-Sair” a comprehensive text addressing war and peace, and “Kitab al-Jihad”, which serves as a guiding light for the preservation of human life during conflict. This article explores in depth the foundational legal principles of warfare within Islamic law as discussed in these significant texts. Keywords: Al-Qur’an, Geneva Convention, Al-sair-ul-Kabir, Civilian, Civilian Rights in War.